Rainwater Harvesting to Augment Groundwater Levels: A Case Study - Machiwal, Deepesh; Ojha, Santosh; Purohit, R. C. (Journal of Agricultural Engineering, 2014)
A rainwater harvesting structure in Rajsamand district in semi-arid region of Rajasthan was evaluated by rainfallwater level dynamics, surface-ground water interaction and potential/actual groundwater recharge. Daily rainfall and evaporation, water level of the water harvesting structure, weekly groundwater levels of ten wells and pre- and post-monsoon groundwater quality were monitored during 2007-10, and analysed. Results indicated that rainfall had strong influence on the surface water and groundwater levels. Groundwater quality was found to be satisfactory for drinking and irrigation purposes. The potential recharge rate in the area was 1 m.day-1. However, the actual groundwater recharge varied from 4.3 to 30.4 cm (8.3-26.1% of monsoon rainfall). Thus, the study reaffirmed that rainwater harvesting structures have adequate potential in rainwater recharging to augment the groundwater levels in the study area.